Estudo de Prevalência de Insuficiência Cardíaca em Portugal (PORTHOS), fundamentação e conceção – um estudo populacional - Baptista, Rui (2023)
Funding Information: PORTHOS study arises from a scientific partnership between the Portuguese Society of Cardiology, AstraZeneca and NOVA Medical School. The authors are especially grateful to all the institutional partners that collaborated at various levels: Associação de Apoio aos Doentes com Insuficiência Cardíaca (AADIC), GlobalSports, Maria Design, Missão Continente (Sonae), Unilabs and GE. For the collaboration in the pilot study, the authors are grateful to Unidade Local de Saúde de Matosinhos (Dr. Nuno Moreno and Dr. Daniel Seabra) and to Câmara Municipal de Matosinhos. We are also grateful to Prof. Artur Paiva and Dr. João Mariano Pêgo from Centro Hospitalar and Universitário de Coimbra. To the members of the study management team for their valuable contribute: Dra. Adriana Salgueiro and Dr. Diogo Pedroso. Publisher Copyright: © 2023 Sociedade Portuguesa de Cardiologia